2014
DOI: 10.1517/14740338.2014.925443
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tuberculosis drugs adverse reactions: a review of the Iranian literature

Abstract: The pattern of ADRs in Iranian articles was found to be similar to many other studies in the present review. We suggest that future studies resolve the confounding factors in this area that are mentioned in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Previous reports of some notable adverse drug reactions include weight increase and hepatotoxicity [29] , [45] , reproductive toxicity [29] , exanthema, hematological [46] among others when RIPE is used either as the sole agent or together. In fact, antituberculosis drug-induced hepatotoxicity has been reviewed [47] . According to WHO report on the Global project on antituberculous drug Resistance Surveillance, adverse effects of RIPE have chopped up into diminishing treatment effectiveness because they significantly contribute to treatment failure while relapse or the emergence of drug-resistance are now routinely encountered [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of some notable adverse drug reactions include weight increase and hepatotoxicity [29] , [45] , reproductive toxicity [29] , exanthema, hematological [46] among others when RIPE is used either as the sole agent or together. In fact, antituberculosis drug-induced hepatotoxicity has been reviewed [47] . According to WHO report on the Global project on antituberculous drug Resistance Surveillance, adverse effects of RIPE have chopped up into diminishing treatment effectiveness because they significantly contribute to treatment failure while relapse or the emergence of drug-resistance are now routinely encountered [48] .…”
Section: Discussionmentioning
confidence: 99%
“…These uncured patients are vulnerable to relapse and may even develop multi-drug resistant TB 1 3 . The lack of a uniform standard method for the determination of cured TB may also lead to over-treatments of some TB patients, causing the augmentation of drug-related mortality 4 . Moreover, chest X-rays and CT scans are subjective tests, and sputum smear cannot distinguish dead from viable bacteria (sensitivity = 19.6%, specificity = 87.0%) 5 , and sputum cultures require 4 to 8 weeks of incubation time (sensitivity = 91.8%, specificity = 57.8%) 6 .…”
mentioning
confidence: 99%
“…Hepatic injury was the most common adverse reaction caused by anti-tuberculosis drugs, as described in other publications [24]. The incidence reported in previous studies vary greatly, from 2 to 28% [27], possibly due to differences in the criteria used to evaluate liver dysfunction, population characteristics and treatment regimens. The rate of drug withdrawal due to liver damage in this study was 22.7%, similar to that reported previously [43].…”
Section: Discussionmentioning
confidence: 86%
“…Adverse reactions caused by anti-tuberculosis drugs are important factors affecting the success of standard therapy for tuberculosis. Previous studies have reported that the total incidence of adverse reactions caused by anti-tuberculosis drugs is 12.6% in China [24], 12.5% in Portugal [25], 17.1% in Korea [26], and 33.6% in Iran [27]. The apparent variation between studies may be related to differences in the incidence of tuberculosis, treatment strategies used or definitions of adverse reactions, as well as other factors.…”
Section: Discussionmentioning
confidence: 99%